2011
DOI: 10.1089/tmj.2010.0208
|View full text |Cite
|
Sign up to set email alerts
|

Change of Patients' Perceptions of Telemedicine After Brief Use

Abstract: These findings show that brief use of a Web-based telemedicine service has a significant positive effect on patients' perceptions of this service. Therefore, as patients do not have prior experience with innovative telemedicine services, offering patients a risk-free way to explore and experiment with the service can increase the development of accurate perceptions and user needs. Ultimately, this will increase patients' acceptance of telemedicine. Future studies should investigate the effect of continued usag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 17 publications
7
31
0
2
Order By: Relevance
“…They provide trustworthy information on, as well as an introduction to IMIs [40,48-51]. To date, 3 RCTs have investigated the influence of a video-based [42,47] or personal [46] AFI in the clinical population of pain [47], diabetes [46], and primary care patients with depressive symptoms [42].…”
Section: Introductionmentioning
confidence: 99%
“…They provide trustworthy information on, as well as an introduction to IMIs [40,48-51]. To date, 3 RCTs have investigated the influence of a video-based [42,47] or personal [46] AFI in the clinical population of pain [47], diabetes [46], and primary care patients with depressive symptoms [42].…”
Section: Introductionmentioning
confidence: 99%
“…It is hypothesized that conditional aspects like the possibility to get access to the service or the way the health care professional puts the service into practice are important for actual use. Building in experience sessions with a telemedicine service for a patient might be useful [28] as well as providing the service via a neighborhood facility instead of directly totally independent at home. Cranen et al [29] showed chronic pain patients prefer this above a home situation.…”
Section: Discussionmentioning
confidence: 99%
“…Practitioners determine Perceived Usefulness by how they suppose ICTs will enhance their job performance (e.g., productivity, quality, effectiveness). Clients determine Perceived Usefulness by how they suppose ICTs will impact the effectiveness of the service they access (Cranen et al 2011). Perceived Ease of Use is the belief by practitioners and clients regarding how easy/difficult or simple/complex ICTs are to use.…”
Section: Understanding Informal Use Of Icts In Clinical Practicementioning
confidence: 99%